PEMANFAATAN SAMPAH ORGANIK MENJADI TEPUNG SEBAGAI BAHAN BAKU PRODUKSI PAKAN IKAN DAN TERNAK - Orbawati, Eny Boedi; Armando, Eric; Tartila, Shobrina Silmi Qori; Jalunggono, Gentur (Jurnal Abdi Insani, 2024)
Wastes can be managed into a good source of energy and animal feed to become more economically valuable and profitable. However, only a small amount of this waste is absorbed as an energy source, and becomes food for fish and animal. Several wastes that can used for animal and fish feed are vegetable waste, fruit waste, household and restaurant food waste, namely waste rice, meat, eggs, bones, coconut dregs, grains, etc. These wastes have the potential to be used as fish and animal feed. The food waste availability is quite abundant and has not been utilized to support the cultivation of fish and animal. These wastes are expected as alternative feed ingredients to cut the feed costs effectively and efficiently. If these ingredients are applied, community service activities are necessary regarding the manufacture of alternative feed ingredients from organic waste for fish and animal feed. The service was carried out in Wonosari, Gunungpring Village, Muntilan District, Magelang Regency, in September – October, 2023. Service participants were 15 residents of Wonosari, four students, and nine lectures from Tidar University. Materials in this service focuses on providing education on the types of organic waste that can be used as feed ingredients. The waste is processed through several stages of drying and milling. This service program increases the efficiency and effectiveness of manufacturing fish and animal feed. Training has an impact on reducing the feed costs effectively through training and community assistance, so that fish and animal farming activities can be carried out efficiently.